ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KOLEKTIBILITAS KREDIT USAHA RAKYAT (KUR) MIKRO BRI (Studi Empiris Pada Debitur KUR Mikro BRI Unit Nita) - Devi Maulani, Elisabeth; Nona Dince, Maria; Rangga, Yoseph Darius Purnama (Jurnal Projemen UNIPA, 2025)
Credit collectibility is one of the indicators to assess a bank's performance. The debtor's ability to repay credit does not always run smoothly, which can affect credit collectibility. The purpose of this research is to determine the influence of business experience, business income, collateral value, number of dependents, and repayment period on the credit collectibility of people's business. This study uses a quantitative approach with an empirical study on debtors of the People's Business Credit (KUR) Micro at Bank BRI Unit Nita, employing area sampling techniques since the population is spread across a specific geographic area. The number of samples used is 34 KUR Micro debtors from BRI Unit Nita located in Nita Kloang Village. Data were collected through a questionnaire using a Likert scale and analyzed using multiple linear regression with the help of SPSS software. The results show that partially only the business experience variable has a significant influence.